The Correlation between Occupational Stress and Job Performance of Healthcare Workers at the University of Jember Medical Center - Arista Nur Isnaini; Inke Kusumastuti; Ida Srisurani Wiji Astuti (Journal of Agromedicine and Medical Sciences, 2021)
Healthcare professionals are prone to experiencing stress and burnout due to their responsibility to care for one’s life and mistakes in the care delivery might lead to dire consequences for the patient. Occupational stress in the healthcare service could reduce the job performance of healthcare workers. This study was therefore conducted to determine the effect of occupational stress on the performance of healthcare workers in the University of Jember Medical Center. This study employed a cross-sectional design. The research sample was 28 healthcare workers at the University of Jember Medical Center. The results of the Pearson test showed a significance value of p = 0.725, indicating no significant correlation between occupational stress and job performance of health workers at the University of Jember Medical Center. Occupational stress might be experienced by healthcare workers at University of Jember Medical Center because University of Jember Medical Center as the first level of healthcare facilities acts as a gatekeeper with significant workload and functions. However, this occupational stress didn’t affect the work performance of the healthcare workers at University of Jember Medical Center due to their excellent stress management. Future studies might benefit from utilizing other more objective stress-related measurements and recruiting larger sample size. Keywords : Occupational stress, Job Performance, Healthcare Worker